2014
DOI: 10.11648/j.pbs.20140302.14
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Peer-Pressure as Predictors of Substance Abuse among University Students

Abstract: Abstract:The study investigated the prevalence of substance abuse and its prediction by parenting styles and peer pressure among university students. Participants in this cross-sectional survey consisted of four hundred and fifty two randomly selected undergraduates of Olabisi Onabanjo University (OOU), Ago-Iwoye. The sample consisted of 221 (48.9%) males and 231 (51.1) females. Participants' age ranges were as follow: 126 (27.9%) were aged between 18 and than 20 years, 312 (69.0%) were aged between 20 and 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…According to our results, peer pressure is the primary catalyst for drug addiction in the Karachi population similar to studies done in other parts of the world [12,13]. Curiosity, the second highest motive behind drug abuse as per current results, remains consistent with similar studies done in other populations [14].…”
Section: Discussionsupporting
confidence: 91%
“…According to our results, peer pressure is the primary catalyst for drug addiction in the Karachi population similar to studies done in other parts of the world [12,13]. Curiosity, the second highest motive behind drug abuse as per current results, remains consistent with similar studies done in other populations [14].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, peer support seems to protect students' mental health (Alsubaie et al, 2019 ): indeed, those who report higher levels of perceived social support, also report lower levels of all types of loneliness (Bernardon et al, 2011 ). Besides, university students' well-being can be also influenced by peer pressure (Alsubaie et al, 2019 ), that seems to have a role in increasing alcohol and drug consumption (Knee and Neighbors, 2002 ; Monaci et al, 2013 ; Abikoye et al, 2014 ), body image concerns (Webb and Zimmer-Gembeck, 2014 ), and internet addiction (Esen and Gündogdu, 2010 ). At the same time, family emotional support seems to have a great importance on happiness and life satisfaction (North et al, 2008 ; Delle Fave et al, 2010 ; Hsu, 2010 ).…”
mentioning
confidence: 99%
“…Parenting style has been found by various studies to predict child well-being in the domains of social competence, academic performance, psychosocial development and become adaptive, well-functioning members of the society [17,28]. Comparative studies on different parenting styles have also shown that authoritative style is the best and most common and children from authoritative parents have a better social skill, better work ethic and academic performance and less involved in substance abuse than those whose parents are non-authoritative [29,30,31]. Also, imposing a particular rule is the parenting practice, but how the rule is implemented and communicated to the child is influenced by the parenting style.…”
Section: Discussionmentioning
confidence: 99%